Cover Feature: Demonstrating the Use of a Fungal Synthesized Quinone in a Redox Flow Battery (Batteries & Supercaps 1/2023). Issue 1 (15th December 2022) - Wilhelmsen, Charlotte Overgaard; Kristensen, Sebastian Birkedal; Nolte, Oliver; Volodin, Ivan A.; Christiansen, Johan Vormsborg; Isbrandt, Thomas; Sørensen, Trine; Petersen, Celine; Sondergaard, Teis Esben; Lehmann Nielsen, Kåre; Larsen, Thomas Ostenfeld; Frisvad, Jens Christian; et al.
Abstract : The Cover Feature illustrates a redox flow battery based on the fungal pigment phoenicin, which was produced and extracted from Penicillium atrosanguineum . The yield of this bibenzoquinone was >1 g L −1, which demonstrates that functional electrolytes can be produced sustainably in microorganisms and thereby contribute to the green transition. More information can be found in the Research Article by C. O. Wilhelmsen, J. Muff, J. L. Sørensen and co‐workers .